Matharpacady-06.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Typically, staircases are located on the outside. This saved space inside the houses and allowed independent access to tenants living on the first floor. Originally, balconies were open and had a wooden or metal balustrade running around. Over time, some balconies have been enclosed with metal grilles fitted from outside, which allow the space to be utilized for storing plants or serve as an extension of the living quarters.